Tecnologia social e gestão social: interfaces e conexões - Duque, Thais Oliveira (2015)
The overall objective in this dissertation, which is organized in the form of scientific papers, was to examine the theoretical and empirical constructs of Social Technologies in the Brazilian context and how they interrelate with the Social Management. Specifically, the objectives were: a) analyze the possible theoretical aspects underlying the term „social technology‟; b) punctuate the differences between Strategic Management and Social Management and create, similarly, the same comparative framework for Conventional Technology and Social Technology c) propose that the Social Technologies can be an emancipatory way in the creation and dissemination of public policies, as an example of sociological reduction, as enunciated Guerreiro Ramos, promoting the choice of possibilities arising from the society. The second part presents three articles. In the first article, the main objective was to analyze the possible theoretical aspects underlying the term „social technology‟. To meet this goal we used the technique of bibliometrics and Google Scholar as a support tool. It was found the presence of two theoretical perspectives: i) the first, the main precursor is the teacher Renato Dagnino who considers that the Social Technology is not only an artifact or a technique, but a social construct that provides for the growing community; ii) the second stream identified has Silvio Caccia Bava as its first author and uses the term social technology to identify technologies for social, ie, techniques, programs, procedures, used to fix social ills of communities, either within the health, education or public safety. In the second article we scored the differences between Strategic Management and Social Management and created a comparative table to Conventional Technology and Social Technology in order to establish the Social Technology and Social Management tool. The path to fulfill that purpose was to first, examine the settings on the Social and Social Technology Management to subsequently present the comparative tables of terms. The above considerations refer to legitimate-looking statements by the following methodological approach and the works that support it, but we consider only the first step for these two concepts to be part of the same theoretical construct and a form of articulation to strengthen the public policy field in the country and as well as to fulfill its social and political function. The third article discusses the need and the possibility of establishing a substantive rationality to society, using the P and N Theory of Alberto Guerreiro Ramos‟ theory to analyze the Brazilian public administration. This theory has been used as a methodology by Zwick (2012), joining Alberto Guerreiro Ramos and coining the term „Tupiniquim Public Administration‟. From this premise we formulated the hypothesis that social technologies are objective possibilities in the construction of public policies in Brazil. Upon completion of the foundation about the concepts „Social Technology‟, P Theory and N Theory, Sociological reduction and the creation of public policies, we can reflect on the current Brazilian context and together with the concept of Tupiniquim public service make chorus with Alberto Guerreiro Ramos‟ theories. Social Technologies being considered a tool for the creation of public policies in this scenario. It was not the aim of this paper to point out the best or most convenient form of technology. The goal was to show their differences, first establishing social technology, then combining to it the social management and, finally, presenting the social technology as a model for public management. It is considered anyway that further work is needed involving empirical research to assess what kind of management and what kind of technology is being used by governments and non-governmental non-profit organizations. This is because the wrongly made management causes social problems, affecting significantly the society.